Rehabilitation strategy for hip fracture, focused on behavioral psychological symptoms of dementia for older people with cognitive impairment: A nationwide Japan rehabilitation database - Shibasaki, Koji (PLoS One, 2018)
The aim is to investigate the relationship between a positive outcome on rehabilitation after hip fracture and behavioral psychological symptoms of dementia (BPSD) transition during rehabilitation. This study is a retrospective cohort study based on the Japan Rehabilitation Database. We recruited 756 subjects 65 years of age or older from 31 hospitals in the database. All subjects were in the hospital as patients undergoing rehabilitation for hip fracture. Functional independence measure (FIM), walking ability, Mini-Mental State Examination (MMSE), and BPSD were measured both at the beginning and at the end of rehabilitation. MMSE for 23 or under was defined as the cognitive-impaired group. MMSE for 24 or over was used as the cognitively intact group. Cognitive impaired participants were divided into four groups: participants presented no BPSD both at the beginning of rehabilitation and at the end of rehabilitation (Group (-/-)), participants presented BPSD at the beginning of rehabilitation but resolved at the end of rehabilitation (Group (+/-)), participants had no BPSD at the beginning of rehabilitation but appeared at the end of rehabilitation (Group (-/+)) and participants had sign of BPSD both at the beginning of rehabilitation and at the end of rehabilitation (Group (+/+)). The endpoints were waking ability, FIM gain. As results, one hundred thirty-seven cognitive-impaired older people patients out of 471 (29.1%) suffered from BPSD at the beginning of rehabilitation. FIM gains in cognitively intact group, Group (-/-), Group (+/-), Group (-/+) and Group (+/+) were 24.8 ± 18.7, 17.5 ± 16.9, 27.3 ± 19.7, 17.8 ± 12.2 and 12.2 ± 17.2, respectively. The Group (+/-) was significantly connected to a positive outcome for rehabilitation. The present study suggested that the management of BPSD can lead to better functional recovery during rehabilitation.